Preparation and In vitro Evaluation of Folated Pluronic F87/TPGS Co-modified Liposomes for Targeted Delivery of Curcumin - Li, Wenjuan; Xiong, Xiangyuan; Gong, Yanchun; Li, Ziling (Current Drug Delivery, 2024)
Background: Using targeted liposomes to encapsulate and deliver drugs has become a hotspot in biomedical research. Folated Pluronic F87/D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) co-modified liposomes (FA-F87/TPGS-Lps) were fabricated for curcumin delivery, and intracellular targeting of liposomal curcumin was investigated. Methods: FA-F87 was synthesized and its structural characterization was conducted through dehydration condensation. Then, cur-FA-F87/TPGS-Lps were prepared via thin film dispersion method combined with DHPM technique, and their physicochemical properties and cytotoxicity were determined. Finally, the intracellular distribution of cur-FA-F87/TPGS-Lps was investigated using MCF-7 cells. Results: Incorporation of TPGS in liposomes reduced their particle size, but increased the negative charge of the liposomes as well as their storage stability, and the encapsulation efficiency of curcumin was improved. While, modification of liposomes with FA increased their particle size, and had no impact on the encapsulation efficiency of curcumin in liposomes. Among all the liposomes (cur-F87-Lps, cur-FA-F87-Lps, cur-FA-F87/TPGS-Lps and cur-F87/TPGS-Lps), cur-FA-F87/TPGS-Lps showed highest cytotoxicity to MCF-7 cells. Moreover, cur-FA-F87/TPGS-Lps was found to deliver curcumin into the cytoplasm of MCF-7 cells. Conclusion: Folate-Pluronic F87/TPGS co-modified liposomes provide a novel strategy for drug loading and targeted delivery.
Keywords: Folate